The care and management of lies : a novel of the Great War - Winspear, Jacqueline, 1955- (Harper Perennial, 2015)
"By July 1914, the ties between Kezia Marchant and Thea Brissenden, friends since girlhood, have become strained--by Thea's passionate embrace of women's suffrage, and by the imminent marriage of Kezia to Thea's brother, Tom, who runs the family farm. When Kezia and Tom wed just a month before war is declared between Britain and Germany, Thea's gift to Kezia is a book on household management--a veiled criticism of the bride's prosaic life to come. Yet when Tom enlists to fight for his country and Thea is drawn reluctantly onto the battlefield, the farm becomes Kezia's responsibility. Each must find a way to endure the ensuing cataclysm and turmoil. As Tom marches to the front lines, and Kezia battles to keep her ordered life from unraveling, they hide their despair in letters and cards filled with stories woven to bring comfort. Even Tom's fellow soldiers in the trenches enter and find solace in the dream world of Kezia's mouth-watering, albeit imaginary meals. But will well-intended lies and self-deception be of use when they come face to face with the enemy?"--Back cover.